ANALISIS KUALITAS PELAYANAN AKADEMIK DAN ADMINISTRASI TERHADAP KEPUASAN MAHASISWA DAN ALUMNI PADA MASA PERALIHAN SEKOLAH TINGGI AGAMA ISLAM NEGERI (STAIN) MENJADI INSTITUT AGAMA ISLAM NEGERI (IAIN) BATUSANGKAR - Sri Adella Fitri (IAIN Batusangkar, 2018)
So far, various performance measurements have been done by IAIN Batusangkar, for example, through Annual Working Report, which illustrates the achievement of targets that have been planned. The development of one of the performance measurements that focuses on measuring the performance of non-financial IAIN is from the consumer view-point namely the students and alumni. It is expected to be able to provide comprehensive improvement on the satisfaction of students and alumni on the quality of service that has been given IAIN, good quality of administration services, quality of service teaching and learning process and all academic processes that have been experienced. This research is a field research i.e., descriptive quantitative, that is explaining satisfaction and loyalty of the students and alumni to the quality of academic and administrative services in the transition period from State College for Islamic Studies (STAIN) to become State Institute for Islamic Studies (IAIN) Batusangkar. Based on the calculation of the students' and the alumni's satisfaction, it was found that the obtained total satisfaction was 67.96%, and 76.84%. It means that the consumers' satisfaction (in this case students' and alumni's) on the performance of IAIN Batusangkar has not satisfactory.